Immunohistochemical expression of PD-L1 in esophageal carcinoma and its correlation with histopathological features - Tarunpreet Saini; Manisha Sharma (Journal of Pathology of Nepal)
Background: Carcinoma of the esophagus poses a considerable medical and public health challenge in many parts of the world. Despite advances in screening and multimodal management of this disease, overall survival remains poor. There is an utmost need to find a marker for the establishment of targeted immunotherapy. One immunohistochemical marker that has surfaced with the advent of anti-PDL1 immunotherapy is PD-L1 which has been proven to be advantageous. This study aimed to determine PD-L1 expression and its correlation with the grade of tumor and other histopathological parameters in 50 patients.